Sources of glycerol dialkyl glycerol tetraethers (GDGTs) in catchment soils, water column and sediments of Lake Rotsee (Switzerland) – Implications for the application of GDGT-based proxies for lakes - Naeher, Sebastian; Peterse, F.; Smittenberg, R.; Niemann, H.; Zigah, P.; Schubert, C. (Pergamon, 2014)
We analysed glycerol dialkyl glycerol tetraether (GDGT) distributions in the water column, sediment and catchment soils of the Swiss Lake Rotsee to determine the sources of GDGTs in the lake sediment and to determine the implications for GDGT-based palaeoclimate proxies. The branched GDGT (brGDGT) distribution in the soils surrounding the lake showed significant heterogeneity, which may be partly explained by vegetation cover and soil moisture. One group of soils seems to provide the largest contribution of soilderived GDGTs to the lake, or the distribution of GDGTs in these soils is affected by the relatively high soil moisture availability, creating lake-like conditions and GDGT distributions. Comparison of GDGT distributions in soils, water column and sediments indicated that brGDGTs and crenarchaeol in the sediment are partly soil derived, but that in situ production in the water column and/or sediment also takes place. Eutrophication seems to affect the distributions of brGDGTs by dilution of the supply of soil derived brGDGTs to the lake and by changing the degree of in situ production of brGDGTs in the water column. Furthermore, the eutrophic conditions in the lake promote methanogenic activity and subsequently cause a contribution of isoprenoid GDGTs (isoGDGTs) of methanogenic origin to the sediments. The aquatic production of GDGTs has implications for the reliability of GDGT-based proxy results. In particular, the application of the BIT and TEX86 indices is hampered by the mixed sources of the GDGTs in the lake. In contrast, global lake-specific brGDGT-based temperature calibrations resulted in temperature estimates that resemble measured mean annual and summer air temperatures. CBT-derived pH values agreed well with measured soil and water column values. Our results demonstrate that understanding the source ofGDGTs in lake sediments is important for thWe analysed glycerol dialkyl glycerol tetraether (GDGT) distributions in the water column, sediment and catchment soils of the Swiss Lake Rotsee to determine the sources of GDGTs in the lake sediment and to determine the implications for GDGT-based palaeoclimate proxies. The branched GDGT (brGDGT) distribution in the soils surrounding the lake showed significant heterogeneity, which may be partly explained by vegetation cover and soil moisture. One group of soils seems to provide the largest contribution of soil-derived GDGTs to the lake, or the distribution of GDGTs in these soils is affected by the relatively high soil moisture availability, creating lake-like conditions and GDGT distributions. Comparison of GDGT distributions in soils, water column and sediments indicated that brGDGTs and crenarchaeol in the sediment are partly soil derived, but that in situ production in the water column and/or sediment also takes place. Eutrophication seems to affect the distributions of brGDGTs by dilution of the supply of soil derived brGDGTs to the lake and by changing the degree of in situ production of brGDGTs in the water column.e robust interpretation of palaeoclimate records obtainedfrom downcore proxy applications.Furthermore, the eutrophic conditions in the lake promote methanogenic activity and subsequently cause a contribution of isoprenoid GDGTs (isoGDGTs) of methanogenic origin to the sediments. The aquatic production of GDGTs has implications for the reliability of GDGT-based proxy results. In particular, the application of the BIT and TEX86 indices is hampered by the mixed sources of the GDGTs in the lake. In contrast, global lake-specific brGDGT-based temperature calibrations resulted in temperature estimates that resemble measured mean annual and summer air temperatures. CBT-derived pH values agreed well with measured soil and water column values. Our results demonstrate that understanding the source of GDGTs in lake sediments is important for the robust interpretation of palaeoclimate records obtained from downcore proxy applications.